An integrated electrical drive control laboratory: Speed control of induction motors - Dandil, Besir (Wiley, 2012)
This paper presents an integrated environment for speed control of vector controlled induction motor (IM) including simulation and experimental study. In the prepared integrated environment, students and researchers can realise the speed control of IM by selecting the classical controllers such as proportional?+?integral?+?derivative (PID) and integral?+?proportional (IP) or intelligent controllers such as fuzzy (FC), neural network (NNC) and neuro-fuzzy (NFC). Users can perform simulation and experimental studies on-line to evaluate performance of the control system under parameter and load variations in IM drive. The integrated environment allows users to compare simulation and experimental results and evaluate basic distinctions between classical and intelligent controllers. Furthermore, performance of the controller designed by the user can be tested on-line. Important variables of drive system can be monitored as graphically or saved as digitally for further processing by using the designed graphical user interface (GUI). (c) 2010 Wiley Periodicals, Inc. Comput Appl Eng Educ 20: 410418, 2012
Keywords: integrated education; induction motor; vector control; neuro-fuzzy control